2020
DOI: 10.1021/jacs.9b12073
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics of CdSe Quantum-Dot-Doped Glasses

Abstract: We have probed the local atomic structure of the interfacial structure between the CdSe quantum dots (QDs) and sodium silicate glass matrix. Using ab initio molecular dynamics simulations, we determined the structural properties and bond length, in excellent agreement with previous experimental observations. Based on analysis of radial distribution functions, coordination environment and ring structures, we demonstrate that huge structure reconstruction occurs at the interface between the CdSe QDs and the glas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In later work, we created a more detailed atomic structure by using a combination of classical and ab initio molecular dynamics, demonstrating the complex interfacial chemical environment between the CdSe quantum dot and a surrounding glass matrix. 13 In the present work, we used DFT-based methods to determine the structure of CdSe quantum-dot-doped glasses with varying composition, and calculate their electronic structure to probe the impact of the glass matrices on the optical properties of the CdSe quantum dot. Besides, the sodium ion was found to sharply decrease the HOMO-LUMO gap in previous DFT calculations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In later work, we created a more detailed atomic structure by using a combination of classical and ab initio molecular dynamics, demonstrating the complex interfacial chemical environment between the CdSe quantum dot and a surrounding glass matrix. 13 In the present work, we used DFT-based methods to determine the structure of CdSe quantum-dot-doped glasses with varying composition, and calculate their electronic structure to probe the impact of the glass matrices on the optical properties of the CdSe quantum dot. Besides, the sodium ion was found to sharply decrease the HOMO-LUMO gap in previous DFT calculations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The generation of CdSe QD embedded in glass matrices is involved in 3 steps as developed in our previous study. 38 Firstly, the glass matrices with composition of 25 Na2O-75 SiO2, 33 Na2O-67 SiO2, 20 Na2O-5 CaO-75 SiO2, and 15 Na2O-10 CaO-75 SiO2 (mol%) were generated by classical MD using the DL_POLY code. 57 A partialcharge rigid-ion pairwise potential developed by Pedone et al 58 was used to perform the simulations.…”
Section: Creating the Atomic Structure Of Cdse Qds Embedded In Inorga...mentioning
confidence: 99%
“…The size-dependent band gap of QDs in different matrices has been studied based on potential-morphing method (PMM): 37 it was found that the confining potential depends exclusively on the nature of the matrix (and not on that of the dot). Furthermore, our own previous work 38 suggested that the QDs could not maintain their ideal structure -even at their core -when they were incorporated into glass matrices, in stark contrasts with colloidal QDs (which feature a slight rearrangement for surface atoms and maintain their bulk structure at the core). For CdSe QDs in binary alkali silicate glasses, the breakage of stable 6-member and 4-member Cd-Se rings was observed, with the formation of Se-Na or Cd-O interfacial linkages.…”
Section: Introductionmentioning
confidence: 97%
“…The diffusion kinetics of precursor ions of CsPbX 3 QDs can be changed by adjusting the glass network structure [ 26 , 27 , 28 , 29 ], which affects the optical properties of the QDs in a glass matrix. The heterogeneous pair-bonds are existing on the interface between the QDs and the glass matrix [ 30 , 31 , 32 ], which leads to the formation of defects on the QDs surface, thus affecting the optical properties of the QDs embedded in the glass matrix. In addition, the stability of CsPbX 3 QDs in different glass matrixes is also distinct, which is believed to be determined by the resistance against hydration and oxygen of the glass matrix itself.…”
Section: Introductionmentioning
confidence: 99%